2014
DOI: 10.1097/ico.0000000000000038
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Quality of Life Measures in Dry Eye Questionnaires

Abstract: Purpose Dry eye disease (DED) is an ocular disease that affects 5% to 17% of the US population. Because of the negative effects of DED on patients’ quality of life (QOL), disease-specific questionnaires that assess QOL in patients with dry eyes are essential in the monitoring and management of this chronic ocular condition. This review provides clinicians and researchers with a summary of the current questionnaires available for assessing QOL in patients with dry eyes. Methods A systematic review of the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
123
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(129 citation statements)
references
References 23 publications
2
123
0
4
Order By: Relevance
“…To our knowledge, this is the first evaluation of how prediagnosis history impacted patients' lives, an aspect left out of existing questionnaires on DED-related symptoms/QoL 20 21. We also gathered language-specific information on keywords used by patients to spontaneously describe their ocular condition.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first evaluation of how prediagnosis history impacted patients' lives, an aspect left out of existing questionnaires on DED-related symptoms/QoL 20 21. We also gathered language-specific information on keywords used by patients to spontaneously describe their ocular condition.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other questionnaires, the OSDI is a more convenient option for clinical use because of its shorter completion time. 31 The low agreement between patient and clinician assessment may indicate that ophthalmologists in Taiwan need better and more accurate quantitative tools to improve the concordance in severity assessment. To date, there is no available universally accepted gold standard test that is reliable to assess dry eye severity.…”
Section: Discussionmentioning
confidence: 99%
“…Differences when compared with patients assigned to a placebo group were statistically significant for both the physical and mental components of the SF-36 weighed against baseline. In the present study, we used a generic HRQoL instrument instead of generic visual function or specific dry eye questionnaires 26. A number of studies have shown the detrimental effect of dry eye syndrome on vision-related quality of life 2729.…”
Section: Discussionmentioning
confidence: 99%